2007
DOI: 10.1080/02699050701553221
|View full text |Cite
|
Sign up to set email alerts
|

Parental alcohol misuse is a powerful predictor for the risk of traumatic brain injury in childhood

Abstract: It was observed that parental alcohol misuse is a major risk factor for TBI in children and drinking to intoxication is a common drinking pattern of adolescents who have sustained TBI in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…Evidence from questionnaire-based studies has suggested that parental alcohol consumption may be directly related to risk of childhood injury [25], [26], [28] and our data have shown that adults’ hazardous or harmful alcohol consumption has an important contribution to the burden of childhood thermal injury and poisonings on a population level, with 32% and 43% of these injuries being attributable to household alcohol misuse.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Evidence from questionnaire-based studies has suggested that parental alcohol consumption may be directly related to risk of childhood injury [25], [26], [28] and our data have shown that adults’ hazardous or harmful alcohol consumption has an important contribution to the burden of childhood thermal injury and poisonings on a population level, with 32% and 43% of these injuries being attributable to household alcohol misuse.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies have identified that individual [9]-[17], family [11][28] and community level factors [9]-[15], [17], [29][32] contribute to children’s risk of injury yet the actual contributions of these factors to the burden of children’s injuries in the general population remain unclear. Most studies were conducted in small geographic areas [9], [11], [13], [15], [19], [22], [31] and used only injuries reported to secondary care [9], [10], [12], [13], [15], [16], [18], [20], [23], [30][32] which represent a highly select group of injuries at the severe end of the spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Parental substance abuse is well established as a risk factor for numerous poor outcomes in children (Dawe et al 2000). Such children are known to experience higher rates of maltreatment, neglect, physical and sexual abuse, behavioral and socio-emotional problems (Dawe et al 2000;Luthar et al 1998;Wilens et al 1995;Hussong et al 2007; Moe et al 2008;Winqvist et al 2007). This paper reports on the evaluation of a child-focused intervention aiming to improve child outcomes called Supporting Kids And Their Environment (SKATE) that has been designed as a supplement to their parents receiving treatment for substance abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Risk of injuries has been found to be over twofold among children of alcohol‐abusing mothers and almost threefold in families where both parents abused alcohol compared with children of abstaining mothers [6]. Brain injuries have also been found to be twice as common among children of alcohol‐abusing parents compared with the control group [7].…”
Section: Introductionmentioning
confidence: 99%